Application of the Plan–Do–Check–Act Cycle in Shortening the Decision to Delivery Interval Time - Lu MN; Zhang BL; Dai QH; Fu XH (Dove Medical Press, 2022)
Ming-Na Lu, Bai-Lei Zhang, Qiao-Hong Dai, Xian-Hu Fu Department of Obstetrics and Gynecology, Ningbo Women and Children's Hospital, Ningbo, 315012, People's Republic of ChinaCorrespondence: Qiao-Hong Dai, Department of Obstetrics and Gynecology, Ningbo Women and Children's Hospital, Ningbo, 315012, People's Republic of China, Tel +86 13858220557, Email daiqiaohongdqh@126.comObjective: To discuss the application value of the plan-do-check-act (PDCA) cycle in shortening the decision to delivery interval (DDI) time.Methods: A total of 106 DDI cases from the Ningbo Women and Children's Hospital (China) from January 2019 to December 2020 were selected as the subjects of this study. The causes for the prolongation of DDI were analyzed and protocols were developed. Through continuous summaries and improvement, a standardized process was established to direct clinical application, ie, the PDCA cycle.Results: The DDI was shortened from 14.26 min in 2019 to 12.18 min in 2020 and the neonatal asphyxia rate significantly decreased from 34.69% in 2019 to 12.50% in 2020 (P < 0.05).Conclusion: The PDCA cycle management mode effectively shortened the DDI time and reduced the neonatal asphyxia rate, without increasing adverse maternal outcomes.Keywords: PDCA cycle, emergency C-delivery, DDI, neonatal, asphyxia